STUDY OF HETEROSIS FOR IMPROVEMENT IN AEROBIC RICE (ORYZA SATIVA L.) - D. A. SHINDE,; P. B. PATEL, (The Bioscan, 2014)
A field experiment was conducted to study the magnitude of heterosis among forty cross combinations developed trough line x tester mating design from four lines and ten aerobic rice testers. In general, it is observed that most of the characters exhibited high heterotic response and existence of substantial amount of genetic variability among parents and hybrids. Highest heterotic effect for grain yield per plant was exhibited by cross combination NVSR-178 x NAUR-1 (49.89 %) followed by hybrid NVSR-178 x IET-21682 (44.17 %) and IR-28 x NAUR-1 (39.51 %). It was also observed from present study that heterotic response for grain yield per plant was mainly due to high heterotic response observed for productive tillers per plant, panicle length, number grains per panicle and test weight. It is clear that yield attributing characters plays major role in yield maximization simultaneously, best performing genotypes such as NVSR-178 and NAUR-1 could be the potential source of breeding material for improvement in aerobic rice.